Defect Self‐Compensation for High‐Mobility Bilayer InGaZnO/In2O3 Thin‐Film Transistor. (18th April 2019) - He, Jiawei; Li, Guoli; Lv, Yawei; Wang, Chunlan; Liu, Chuansheng; Li, Jinchai; Flandre, Denis; Chen, Huipeng; Guo, Tailiang; Liao, Lei
Abstract: Here, the bilayer InGaZnO/In2 O3 thin‐film transistors (TFTs) are deposited by radio‐frequency magnetron sputtering at room temperature. A high field‐effect mobility (μFE ) of 64.4 cm 2 V −1 s −1 and a small subthreshold swing (SS) of 204 mV per decade are achieved in the bilayer‐stack TFTs fabricated upon SiO2 /Si substrate, with large improvement compared to the single‐layer InGaZnO and In2 O3 TFTs. Implementing HfO2 and Si3 N4 as high‐ k gate dielectrics, μFE and SS are correspondingly enhanced to be 67.5 and 79.1 cm 2 V −1 s −1, and 85 and 92 mV per decade in the bilayer TFTs. Defect self‐compensation effect is also revealed, i.e., (In) + + (O) − → In − O, while, respectively, considering the indium‐ and oxygen‐related defects in InGaZnO and In2 O3 and exploring the numerical simulations in SILVACO/Atlas (for electrical performance) and Quantum Espresso (for physical analysis). The InO formation can result in a significant reduction in defect density (validated by the X‐ray photoelectron spectra and low‐frequency noise characterizations) and therefore improvement of μFE and SS in the bilayer‐stack TFT. The important role of defect self‐compensation mechanism while combining different individual channel layers in the oxide semiconducting TFTs is underlined and highly potential application in next‐generation, fast‐speed flexible displays is shown. Abstract : A bilayer InGaZnO/In2 O3 thin‐film transistor is fabricated by radio‐frequency magnetron sputtering with significantly enhanced field‐effect mobility, compared to the single‐layer structure. Defect self‐compensation mechanism is revealed, i.e., (In) + + (O) − → InO, via the low‐frequency noise and X‐ray photoelectron spectra characterizations and the simulations in SILVACO and Quantum Espresso, identifying the decreased defect density and the InO bond formation.